Mapping Pathological Phenotypes in Reelin Mutant Mice - Michetti, Caterina; Romano, Emilia; Altabella, Luisa; Caruso, Angela; Castelluccio, Paolo; Bedse, Gaurav; Gaetani, Silvana; Canese, Rossella; Laviola, Giovanni; Scattoni, Maria Luisa (Frontiers in Pediatrics, 2014)
Autism Spectrum Disorders (ASD) are neurodevelopmental disorders with multifactorial origin characterized by social communication and behavioural perseveration deficits. Several studies showed an association between the reelin gene mutation and increased risk of ASD and a reduced reelin expression in some brain regions of ASD subjects, suggesting a role for reelin deficiency in ASD etiology. Reelin is a large extracellular matrix glycoprotein playing important roles during development of the central nervous system. To deeply investigate the role of reelin dysfunction as vulnerability factor in ASD, we investigated the behavioural, neurochemical and brain morphological features of reeler male mice. We recently reported a genotype-dependent deviation in ultrasonic vocal repertoire and a general delay in motor development in reeler pups. We now report that adult male heterozygous reeler mice did not show social behaviour and communication deficits during male-female social interactions. Wildtype and heterozygous mice also showed a typical light/dark locomotor activity profile, with a peak during the central interval of the dark phase. However, when faced with a mild stressful stimulus (a saline injection) only heterozygous mice showed an over response to stress. At the end of the behavioural studies, we conducted high performance liquid chromatography and magnetic resonance imaging and spectroscopy to investigate whether reelin mutation influences brain monoamine and metabolites levels in regions involved in ASD. Low levels of dopamine in cortex and high levels of glutamate and taurine in hippocampus were detected in heterozygous mice, in line with clinical data collected on ASD children. Altogether, our data detected subtle but relevant neurochemical abnormalities in reeler mice supporting this mutant line, particularly male subjects, as a valid experimental model to estimate the contribution played by reelin deficiency in the global ASD neurobehavioural phenotype.